Relationship between Thioredoxin Reductase (TrxR) Levels and Melasma - Risanti, Rinda Chindra; Jusuf, Nelva Karmila; Putra, Imam Budi (Journal of Society Medicine, 2024)
Introduction: Melasma is a common condition of acquired hypermelanosis in dermatology that often occurs in areas of the body exposed to sunlight, especially the face. Thioredoxin Reductase (TrxR) is a key antioxidant system in defense against oxidative stress through disulfide reductase activity that regulates dithiol/disulfide protein balance. High levels/activity of TrxR correlate with melanin formation and tyrosinase activity which provides additional information about the role of cellular antioxidant proteins in melanogenesis which is suspected to be related to the occurrence of melasma. The aim of this study was to determine the relationship between TrxR levels and melasma Method: This study was an observational analytical study with cross-sectional design on 30 melasma patients and 30 controls. Each patient underwent anamnesis, dermatological examination, and blood sampling to assess TrxR levels by ELISA test. These data were analyzed statistically using the Mann Whitney test. Results: This study shows that the most common distribution pattern of melasma was centrofacial in 24 people (80%). The mean TrxR level in melasma was 12.73±11.66 ng/ml. The results of the study showed that there was a relationship between high TrxR levels and melasma (p<0.001). The TrxR mean level based on the duration of suffering from melasma at <5 years was 11.4±2.89, and ≥ 5 years was 14.0±3,18 Conclusion: There is a relationship between TrxR levels and melasma.